Data on factors affecting smallholder uptake of adaptation and coping measures to deal with rainfall variability - Nyberg, Ylva (Swedish University of Agricultural Sciences, 2021)
Rainfall variability is becoming more profound in East Africa. Smallholders relying on rainfed agriculture are particularly affected and need to adapt their farming systems accordingly. This study examined the measures small-scale farmers use to adapt to, or cope with rainfall variability, their rated perceived effectiveness. It also explored limitations to uptake of measures and sources of learning measures. Questionnaire-based interviews were held with 80 smallholder farmers, both female and male, living in Kisumu and Trans Nzoia counties in Kenya who had/did not have access to regular advisory services (denoted trained and non-trained farmers). Trained farmers used more and better adaptation measures in more effective ways than non-trained farmers. Female farmers felt more limited by lack of knowledge than male farmers, while money, land and labour limited the smallholder farmers equally. Few measures were used to overcome limitations, but several limitations were covered within the advisory package used for trained farmers, and therefore large differences were seen not only in numbers of measures, but also in effectiveness of use. Thus advisory services and policy interventions can play important roles in future efforts to improve uptake of measures.

Structured questionnaire-based interviews on the use of management measures were
held individually with 80 smallholder farmers as a continuation of an earlier study on awareness of the same measures. This quantitative approach (e.g. including counts and scores) enabled the study to be broader, involving a greater number of farmers, and also enhancing the generalization of the results. The study was designed to test for differences between farmers regarding regular or sporadic access to advisory services (trained or non-trained farmers), gender (male or female farmers) and biophysical setting (farming in Trans Nzoia or Kisumu). The study had 10 replicates of each of the eight factorial combinations (e.g. trained female farmer in Kisumu or non-trained male farmer in Trans Nzoia).

Variationer i regnförhållanden blir allt vanligare i Östafrika. Småbrukare som förlitar sig på regn i sitt jordbruk påverkas särskilt och måste anpassa sina jordbrukssystem till de nya förhållandena. Denna studie undersökte de åtgärder som småskaliga bönder använder för att anpassa sig till eller hantera nederbördsvariationer, samt åtgärdernas bedömda och upplevda effektivitet. Studien undersökte också begränsningar för användning av åtgärder och källor till inlärningsåtgärder. Enkätbaserade intervjuer hölls med 80 småbönder, både kvinnor och män, bosatta i Kisumu- och Trans Nzoia i Kenya och som hade/inte hade tillgång till regelbundna rådgivningstjänster (här kallade utbildade och icke-utbildade bönder). Utbildade bönder använde fler och bättre anpassningsåtgärder på effektivare sätt än icke-utbildade bönder. Kvinnliga bönder kände sig mer begränsade av bristande kunskap än manliga bönder, medan pengar, mark och arbete begränsade småbönderna lika mycket. Få åtgärder användes för att övervinna begränsningar, men flera begränsningar täcktes i det rådgivningspaketet som används för de utbildade bönderna, och därför såg man stora skillnader inte bara i antalet åtgärder utan också i effektiviteten i användningen. Således kan rådgivningstjänster och politiska insatser spela viktiga roller i framtida insatser för att förbättra användningen av åtgärder.

Strukturerade enkätbaserade intervjuer om användningen av åtgärder hölls individuellt med 80 småbrukare som en fortsättning på en tidigare studie om medvetenhet om samma åtgärder. Detta kvantitativa tillvägagångssätt möjliggjorde att studien involverade ett större antal bönder och förbättrade också möjligheten till generalisering av resultaten. Studien var utformad för att testa skillnader mellan bönder när det gäller regelbunden eller sporadisk tillgång till rådgivningstjänster (utbildade eller icke-utbildade bönder), kön (manliga eller kvinnliga bönder) och biofysisk miljö (jordbruk i Trans Nzoia eller Kisumu). Studien hade 10 replikat av var och en av de åtta faktorkombinationerna (t.ex. utbildad kvinnlig bonde i Kisumu eller icke utbildad manlig bonde i Trans Nzoia).
Data över faktorer som påverkar småskaliga bönders användning av anpassningsmetoder och påtvingade förändringar i produktionen på grund av variationer i regnförhållanden
Keywords: Agricultural and aquaculture facilities; Jordbruks- och vattenbruksanläggningar; gender; kön; climate adaptation measures; klimatanpassningsmetoder; extension; jordbruksrådgivning; Environment and conservation; Miljö och naturvård; Plants and animals; Växter och djur; Agricultural Science; Jordbruksvetenskap; Environmental Sciences and Nature Conservation; Miljö- och naturvårdsvetenskap; Farming; Areella näringar; Climatology / Meteorology / Atmosphere; Klimatologi och meteorologi